Leaving it all to the Resource Management Act 1991: The Demise of the Tort of Private Nuisance - Besier, Antoinette (Victoria University of Wellington Law Review, 2004)
This article examines the development of the tort of private nuisance in New Zealand, with particular reference to the impact of the Resource Management Act 1991. The challenges confronting, and remedies available to, potential nuisance plaintiffs are contrasted with those provided for under the Act. Case studies of potential nuisance situations sourced from local authority files are used to illustrate some likely approaches to nuisance situations. The author argues that recent cases such as Hawkes Bay Protein Ltd v Davidson are sending the tort of private nuisance down the path of obsolescence.